Work on Paper : Young Flemish Artists Exhibition. - University of Maryland, College Park (Brussel : General Commissariat for International Cooperation Flemish Community, 1988)
Honinckx, Nik ; De Clercq, R. Amea ; De Kramer, Enk ; Slock, Lucy ; Fabre, Jan ; Bilquin, Jean ; Hoenraet, Luc ; Ampe, Dominique ; Dierickx, Karel ; Marcase
Work on Paper : Young Flemish Artists Exhibition, Flemish Week at the University of Maryland, Parents Art Gallery, College Park, May 16 - June 20, 1988
boek